2015
DOI: 10.3758/s13414-015-0917-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual space perception at different levels of depth description

Abstract: The main purpose of this study was to determine the effect of the depth description levels required in experimental tasks on visual space perception. Six observers assessed the locations of 11 posts by determining a distance ranking order, comparing the distances between posts with a reference unit, and estimating the absolute distances between the posts. The experiments were performed in an open outdoor field under normal daylight conditions with posts at distances ranging from 2 to 12 m. To directly assess a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…During the estimation of distance, the operation of object boundary differentiation may have not been universally clear (or understood) by participants. To eliminate the potential intervening variables, we therefore suggest re-creating the experiment with more simplistic objects (e.g., a collection of unified gray boxes-a virtual implementation of research from Šikl and Šimeček [66]). The lens of the VR headset may have also introduced some distortion in the perception of distance.…”
Section: Impact Of Findingsmentioning
confidence: 99%
“…During the estimation of distance, the operation of object boundary differentiation may have not been universally clear (or understood) by participants. To eliminate the potential intervening variables, we therefore suggest re-creating the experiment with more simplistic objects (e.g., a collection of unified gray boxes-a virtual implementation of research from Šikl and Šimeček [66]). The lens of the VR headset may have also introduced some distortion in the perception of distance.…”
Section: Impact Of Findingsmentioning
confidence: 99%
“…In addition to testing ordinal depth perception, we evaluated human performance in a ratio depth task, where participants judged the interval of depth separating pairs of surfaces. Prior work has shown that ordinal depth judgements are more precise than interval/ratio judgements (Norman & Todd, 1998;Šikl & Šimeček, 2015), yet interval/ratio estimation is still important for understanding real-world scene structure, and has received scant attention in the literature. As such, we sought to describe the accuracy of both ordinal and interval/ratio depth judgements in real-world scenes.…”
Section: Research Questionmentioning
confidence: 99%